Things as They Seem. (11th July 2019) - Scruton, Roger
Abstract: I respond to the five papers of criticism in this issue of Philosophy . I argue that my cognitive dualism, which may be open to the theological objections levelled by Fiona Ellis, is vindicated by its ability to explain both freedom and inter-personal relations. I defend the inter-subjectivity of aesthetic judgment against Simon Blackburn's argument from 'the acquaintance principle', and my vision of cultural decline against the sceptical arguments of Samuel Hughes. The crucial role played by subjectivity in my fiction, discussed by Alicja Gescinska, enables me to add to David McPherson's account of existential conservatism, with which I largely concur. I end on a note of puzzlement, as to why such innocent arguments should be the target of such implacable hatred.